The polysemia of suicide - Giraldo Osorio, Mónica (Poiésis, 2012)
When we speak about suicide in our minds, the possibility of the death is opened, and with it, the motives that possibly can drive us to the imperious thought of ending life in a "voluntary" way. In them there would surely be desperation, distress, isolation, lack of sense of life, hopelessness, misery, frustration and many other meanings related to fatality.